Digital Media Marketing Strategy to Increase Car Sales - Dharmawan, Donny; Hidayat, Ahmad Rifqi; Nurdiani, Tanti Widia; Azlina, Yunidyawati; Haes, Putri Ekaresty (LPPPIPublishing, 2024)
The trend in used car prices always depends on market conditions, consumer demand, and also the strength of the product itself. Used car sales can still grow in Indonesia because the car ownership ratio is still low and there is a lot of demand from the first time buyer segment. Therefore, used cars are an option for consumers who want cars at more affordable prices. Indeed, it must be admitted that many certain consumers prefer to choose used cars for certain brands or types for various reasons. This research aims to analyze digital media marketing strategy to increase car sales. This type of research is field research. The research informants were 20 used car sales entrepreneurs in Medan City. The analysis method used in this study is the field qualitative method. Based on the research results show that used car sales businesses in Medan City have implemented a marketing strategy through digital media, which means that it can increase car sales.